A unique nanoporous graphene-ZnxCd1−xS hybrid nanocomposite for enhanced photocatalytic degradation of water pollutants. Issue 15 (15th November 2016) - Lou, Shiyun; Wang, Wan; Jia, Xianbin; Wang, Yongqiang; Zhou, Shaomin
Abstract: In this work, a novel in-situ solvothermal reduction route has been made to immobilize nanoporous Znx Cd1−x S aggregates on graphene nanoribbons by using PVP as a stabilizer and thiourea as a sulphur source. The nanoporous ZnxCd1−x S aggregates with diameters of 20–30 nm assembled from Znx Cd1−x S nanocrystals (3–5 nm) are homogeneously anchored on graphene nanoribbons and the unique structure of graphene-Znx Cd1−x S nanocomposites has contributed to large specific surface area (102.1 m 2 g -1 ). Despite the analogous size and configuration, the nanoporous graphene-Znx Cd1−x S hybrid nanocomposites exhibited composition-dependent photocatalytic performances for the degradation of methyl orange (MO) under visible light. In particular, graphene-Zn0.5 Cd0.5 S was capable of nearly completely degrading MO in 150 min. The excellent photocatalytic activity was proposed to arise from the synergy effect between nanoporous Znx Cd1−x S aggregates and graphene, the suitable band gap, intimate interfacial contact, and unique nanoporous structure. Moreover, the work provides a simple strategy to prepare various nanoporous graphene-semiconductor nanocomposites.